2015
DOI: 10.1093/neuonc/nov170
|View full text |Cite
|
Sign up to set email alerts
|

Glioma-derived extracellular vesicles selectively suppress immune responses

Abstract: The differential effects of high and low EV concentrations dictate modulatory effects on PBMCs. These data provide a role for EVs at high concentrations for inducing selective tolerance of an immune response in a tumor setting. This suggests that lymphocytes in patients' circulation are not irreparably impaired, as previously thought, but can be rescued to augment antitumor responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
100
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 46 publications
1
100
0
Order By: Relevance
“…In accordance with Hellwinkel el al. [23], we reported that GSC-derived exosomes downregulate the activation of PBMCs in terms of proliferation and cytokines production. We demonstrated that the proliferation of CD4+ T within PBMCs treated with GSC-derived exosomes was inhibited, whereas there were no significant effects on CD8+ T cells, supporting the results obtained in [34], in which glioma-derived exosomes failed to alter the activation and INF-γ production by CD8+ T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with Hellwinkel el al. [23], we reported that GSC-derived exosomes downregulate the activation of PBMCs in terms of proliferation and cytokines production. We demonstrated that the proliferation of CD4+ T within PBMCs treated with GSC-derived exosomes was inhibited, whereas there were no significant effects on CD8+ T cells, supporting the results obtained in [34], in which glioma-derived exosomes failed to alter the activation and INF-γ production by CD8+ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that exosomes from murine-derived glioblastoma GL26 cell line promote tumor growth by inhibiting the number and function of cytotoxic CD8 + T cells in vivo [22]. Moreover, GBM-derived vesicles affect cytokine output and migratory capabilities of mitogen-stimulated healthy peripheral blood mononuclear cells (PBMCs) [23] and skew the differentiation of peripheral blood-derived monocytes to alternatively activated M2 tumor-supportive macrophages [24]. Although not all the aspects related to the exosome-induced tumor progression and tolerance have been understood, exosomes could represent potential glioma biomarkers and specific targets to improve tumor immunotherapy [25].…”
Section: Introductionmentioning
confidence: 99%
“…EVs are able to modulate angiogenesis, an important factor in cancer progression (26)(27)(28)(29). EVs have also been shown to modulate the anti-tumoral response by affecting the immune response, T-cell activation and natural killer cell induction (30)(31)(32)(33). EVs can also contribute to drug resistance via various mechanisms, including the sequestration of drugs (34,35) and the transfer of proteins or RNA (36)(37)(38)(39) (40)(41)(42)(43)(44)(45).…”
mentioning
confidence: 99%
“…UPN933 cells were cultured from an anaplastic oligodendroglioma (WHO grade III) obtained on a study approved by the Colorado Combined Institutional Review Board (COMIRB), #95-100. Cells were cultured under “stem-cell conditions” as described [15, 97] and in Supplementary Materials. STR analysis and verification were performed in Nov 2014 by the UCCC PPSR.…”
Section: Methodsmentioning
confidence: 99%